2007
DOI: 10.4141/cjas06011
|View full text |Cite
|
Sign up to set email alerts
|

Apparent and standardized ileal digestibility of amino acids in yeast extract and spray dried plasma protein by weanling pigs

Abstract: . 2007. Apparent and standardized ileal digestibility of amino acids in yeast extract and spray dried plasma protein by weanling pigs. Can. J. Anim. Sci. 87: 381-383. The objective of this experiment was to measure the apparent (AID) and standardized (SID) ileal digestibility of crude protein (CP) and amino acids (AA) in yeast extract and spray dried plasma protein (SDPP) by weanling pigs. A casein-based diet, a casein-SDPP diet, a casein-yeast extract diet, and a N-free diet were formulated and fed to weanlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 7 publications
3
13
3
Order By: Relevance
“…The AID and SID values for N and AA in SDPP were comparable to those reported by Mateo and Stein (2007). Thus, the SDPP fed in the current study represented the SDPP well.…”
Section: Discussionsupporting
confidence: 87%
“…The AID and SID values for N and AA in SDPP were comparable to those reported by Mateo and Stein (2007). Thus, the SDPP fed in the current study represented the SDPP well.…”
Section: Discussionsupporting
confidence: 87%
“…Inclusion of YP in weaned pig diets was similarly effective as spray-dried plasma in increasing feed intake and daily gain of piglets over unsupplemented control diets (Carlson et al 2005). Mateo and Stein's (2007) results that the standardized ileal digestibility of AA in YP in pigs 33 to 56 days of age was similar to that of spray-dried plasma may not be applicable to the immediate post-weaning period. To obtain digestibility data in weaned pigs, ileal digesta can be sampled from slaughtered animals; this method was shown to yield similar results to digesta collection from T-canulas (Donkoh et al 1994).…”
Section: Introductionmentioning
confidence: 68%
“…Exogenous nucleotides have been demonstrated to maintain the function of rapidly dividing tissues, stimulate innate immunity, and reduce the incidence of enteric diseases (Uauy 1994;Sauer et al 2011). Nutritionally, furthermore, it has been reported that YP had comparable nutrients digestibility as SDPP (Mateo and Stein 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Yeast-derived protein (YP), enriched with free amino acids, short chain peptides, nucleotides, and inositol (Pereira et al 2012) has been proposed to be a superior protein ingredient as an alternative to SDPP for weaning pigs. As a mixture of yeast cell contents by removing the cell wall from yeast cells (Chae et al 2001), YP possesses similar apparent (AID) and standardized (SID) ileal digestibility of amino acids with SDPP for weanling piglets (Mateo and Stein 2007;Moehn et al 2010). In addition, the bioactive components of YP (nucleotides, etc.)…”
Section: Introductionmentioning
confidence: 99%